Self-reported sexually transmitted infections and related symptoms among women in Ghana - Florence Gyembuzie Wongnaah; Khadijat Adeleye; Augustus Osborne; Richard Gyan Aboagye; Bright Opoku Ahinkorah (PLoS ONE, 2026)
Introduction Sexually transmitted infections (STIs) remain a major public health issue worldwide, particularly in low- and middle-income countries. Among women, STIs are associated with an elevated risk of HIV infection, infertility, and pelvic inflammatory diseases. This study examined the prevalence of self-reported STIs and related symptoms and their associated factors among women in Ghana. Methods Data from the 2022 Ghana Demographic and Health Survey was used for the study. A weighted sample of 12,997 women of reproductive age (15–49 years) was included in the analysis. Four outcome variables were analysed: (1) any STIs, (2) genital discharge, (3) genital sores or ulcers, and (4) a composite measure of any STIs or genital discharge or genital sores/ulcers (STIs and related symptoms). Multivariable binary logistic regression was used to identify the factors associated with self-reported STIs and related symptoms, with results presented as adjusted odds ratios (aORs) and 95% confidence intervals (CIs). The analysis accounted for sampling weights, clustering, and stratification. All analyses were performed in Stata version 17.0. Results The prevalence of self-reported any STIs, genital sores or ulcers, and genital discharge among women in Ghana was 6.4% (95% CI: 5.8–7.1), 9.1% (95% CI: 8.3–10.0), and 21.9% (95% CI: 20.6–23.4), respectively. An estimated 26.7% (95% CI: 25.2–28.2) of women reported STIs and related symptoms. Women aged 40–44 (aOR = 0.70, 95% CI: 0.52–0.93) and 45–49 (aOR = 0.55, 95% CI: 0.40–0.76) had lower odds of self-reporting STIs and related symptoms than those aged 15–19. Women who first had sex at age 17 or older (aOR = 0.81, 95% CI: 0.72–0.91) also had lower odds of self-reporting STIs and related symptoms than those who first had sex at age 16 or younger. Additionally, women with one (aOR = 0.73, 95% CI: 0.61–0.87), two (aOR = 0.68, 95% CI: 0.55–0.85), three (aOR = 0.71, 95% CI: 0.56–0.90), and four or more children (aOR = 0.61, 95% CI: 0.48–0.77) had lower odds of self-reporting STIs and related symptoms compared with those without children. Women who were cohabiting (aOR = 0.81, 95% CI: 0.67–0.98) and those previously married (aOR = 0.78, 95% CI: 0.62–0.98) had lower odds of self-reporting STIs and related symptoms than those who had never been in a union. Conversely, women who engaged in multiple sexual partnerships (aOR = 1.95, 95% CI: 1.48–2.58) and those who visited the health facility in the past 12 months (aOR = 1.21, 95% CI: 1.08–1.35) had higher odds of self-reporting STIs and related symptoms compared with those without multiple sexual partnerships and those who did not visit the health facility in the past year, respectively. Compared with women from the Western region, those from Ahafo (aOR = 1.62, 95% CI: 1.28–2.05) and Northern (aOR = 1.82, 95% CI: 1.45–2.28) regions had higher odds of self-reporting STIs and related symptoms. Conclusion Self-reported STIs and related symptoms are prevalent among women of reproductive age in Ghana, with variations across the regions. Factors associated with self-reported STIs and related symptoms were women’s age, parity, age at first sex, marital status, number of sexual partners, and health facility visits. Targeted sexual health education focusing on high-risk sexual behaviours, as well as region-specific interventions, are needed to help prevent the incidence of STIs and related symptoms.